The Implementasi Program Rehabilitasi Sosial Penyandang Disabilitas Berbasis Komunitas melalui Kampung Inklusi - Rahmawati, Atik; Sari, Intan Puspita; Mubarok, Akhmad Munif (University of Jember, 2024)
The condition of people with disabilities in Banyuwangi Regency still often receives discrimination and negative stigma. The study in Kedungrejo Village, Muncar District, Banyuwangi Regency noted the efforts made by the Banyuwangi Regency Government in its implementation to develop community-based rehabilitation for people with disabilities through inclusion villages in improving the welfare of people with disabilities. This research method uses a qualitative approach with a descriptive type. Data collection included non-participant observation, semi-structured interviews, and documentation. The results of the research show that the implementation of the community-based social rehabilitation program for persons with disabilities through this inclusion village has seven stages, including technical guidance from the East Java Provincial Social Office to the PPKB Social Office of Banyuwangi Regency; socialization by KSM; registration for potential beneficiaries; preparation of activity plans; implementation of activities (assistance in skills training, marketing guidance, facilitation of market access, and procurement of wheelchair assistance); monitoring and evaluation; as well as termination. Keywords: Persons with Disabilities, Community Based Rehabilitation, Inclusion Villages, Program Implementation